(3JMaI GdCMHGH aj efWb GdWjQ hGdOhGHs - (3eMeO Hf Ydj Hf CMeO Hf Ydj Hf NeGQhjg Hf Whdhf GdOeTbqj GdUGdMj GdMfaj, TeS GdOjf , J (B953 (3g` s
(3ChdgG (B:s
+(3hHYO(B: (3agPG JYdjb SejJg GdCMHGH ai efWb GdWjQ hGdOhGH , hde jSCdfi ai LeYg CMO ef GdCUMGH , hCfG cJHJg QLGA GdG jLO GdeSJWGH , hGddg CSGd Gf jYjffi Ydi Pdc Efg GdeYjf dcd eG ajg KhGH s
(3BNQgG (B:s
(3Gddge Efi CSCdc bhJ jhe Hjhe jGQRGb , hCeG GdOQGL aEfg jbhd (B: (3GdQMef Ydi GdYQT GSJhi (B: (3abGdhG jGHf YHGS fTgO Cf dG Edg EdG Gddg hMOg dG TQjc dg , hCf eMeOG YHOg hQShdg , hCSdehG , hMSf ESdGege s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdJGSYs
(3bQf GdfSN (B:s
(3GdbQf GdYGTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B2 - (3U (B140 s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HNW GdeDdas
Keywords: (3GdCOHs